Curimatá: folha SC.23-Z-A - Corrente: folha SC.23-Y-B (Parcial) - Xique-Xique: folha SC.23-Z-B (Parcial) - ARCANJO, João Batista Alves (2001)
Programa Levantamentos Geológicos Básicos do Brasil - PLGB